Model Populasi Pongo abelii dengan Perubahan Daya Dukung Lingkungan - Jabriel, Karsten Maynard; Jamaludin, Muhamad; Zai, Fidelis Nofertinus (Communication in Biomathematical Sciences, 2023)
Pongo abelii is an endangered orangutan species. The reduction of Pongo abelii can be caused by the removal or loss of orangutans from the population and habitat loss. In general, research on population dynamics with changing carrying capacity is rarely done and it is simulated in this study. We adopted the Verhulst logistic model to model the population dynamics of Pongo abelii. This study aimed to see the effect of increasing the carrying capacity on the population of the endangered Pongo abelii species. From the results of this study, it is concluded that for areas other than Tripa Swamp, Siranggas/Batu Ardan, and East Batang Toru (Sarulla), the addition of carrying capacity is one of the effective options that is urgently needed to maintain a large population of orangutans. For the Tripa Swamp, Siranggas/Batu Ardan, and East Batang Toru (Sarulla) areas, suppressing the number of orangutans loss population is needed to maintain the population, which consists of poaching as trade, conflict killing, hunting/food, wounding, and fire. The results of this study can provide suggestions for tackling the declining population of Pongo abelii species by prohibiting the expansion of the species’ habitat